Rural Finance Policies 4 - Considerations in the placement and outreach of microfinance organizations: the case of ASA, BRAC, and PROSHIKA in Bangladesh - Sharma, Manohar; Zeller, Manfred (International Food Policy Research Institute, 2000)
Governments, policymakers, and donors attach a great deal of importance to poverty outreach—the extent to which MFIs serve poor and disadvantaged locations—when evaluating microfinance institutions (MFIs). With the above considerations in mind, IFPRI undertook a study of the service placement of three major NGOs in Bangladesh: the Association of Social Advancement (ASA), the Bangladesh Rural Advancement Committee (BRAC), and Proshika Manobik Unnayan Kendra (PROSHIKA).